Reproductive toxicity of combined effects of endocrine disruptors on human reproduction - Dutta, Sulagna; Sengupta, Pallav; Bagchi, Sovan; Chhikara, Bhupender S.; Pavlík, Aleš; Sláma, Petr; Roychoudhury, Shubhadeep (Frontiers in Cell and Developmental Biology, 2023)
Confluence of environmental, genetic, and lifestyle variables is responsible for deterioration of human fecundity. Endocrine disruptors or endocrine disrupting chemicals (EDCs) may be found in a variety of foods, water, air, beverages, and tobacco smoke. It has been demonstrated in experimental investigations that a wide range of EDCs have negative effects on human reproductive function. However, evidence on the reproductive consequences of human exposure to EDCs is sparse and/or conflicting in the scientific literature. The combined toxicological assessment is a practical method for assessing the hazards of cocktails of chemicals, co-existing in the environment. The current review provides a comprehensive overview of studies emphasizing the combined toxicity of EDCs on human reproduction. EDCs interact with each other to disrupt the different endocrine axes, resulting in severe gonadal dysfunctions. Transgenerational epigenetic effects have also been induced in germ cells, mostly through DNA methylation and epimutations. Similarly, after acute or chronic exposure to EDCs combinations, increased oxidative stress (OS), elevated antioxidant enzymatic activity, disrupted reproductive cycle, and reduced steroidogenesis are often reported consequences. The article also discusses the concentration addition (CA) and independent action (IA) prediction models, which reveal the importance of various synergistic actions of EDCs mixtures. More crucially, this evidence-based study addresses the research limitations and information gaps, as well as particularly presents the future research views on combined EDCs toxicity on human reproduction.